Cause of repetitive fire disaster in informal settlements and the importance of community based disaster risk mitigation - Adiba, Mehnaz Ahmed (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Master in Disaster Management, 2023.